Implementation Of The Codeigniter 3 Framework For The Payment Of "Cafe Tik Tok" Employees Web-Based Bengkulu - Sastya H. Wibowo; Harry Witriyono; Agung Kharisma Hidayah; Regi Saputra (Jurnal Komputer, Informasi dan Teknologi, 2023)
Cafe Tik tok is a franchise engaged in the restaurant sector. In this tick tok cafe, in processing employee salaries, they still use manual calculations and use the Ms.Excel program. This can cause errors in calculating employee salaries and the process of printing employee payslips that takes a long time. In solving this problem, the authors designed an employee payroll information system. In this design, the author uses the PHP programming language, with the database format using MySQL. The result of this design is to produce an application program that will be used to process web-based employee salaries at the tiktok cafe and it is hoped that the company will find it easy to input data and compile payroll reports to be fast and more efficient.